THE INFLUENCE OF FASHION TRENDS AND CONSUMPTIVE BEHAVIOR ON THRIFT CLOTHING PURCHASE DECISIONS AMONG GENERATION Z IN SURAKARTA - Oktaviani, Nawang; Asmawan, Moh. Chairil (Jurnal Manajemen Terapan dan Keuangan, 2026)
This study aims to analyze the partial and simultaneous effects of fashion trends and consumptive behavior on thrift clothing purchase decisions among Generation Z students in Surakarta. The study was conducted using a quantitative design, utilizing primary data collected through online questionnaires completed by individuals who had prior experience purchasing thrift apparel. A total of 120 respondents were selected using purposive sampling. Data analysis was performed using Structural Equation Modeling with the Partial Least Squares method to evaluate both measurement and structural relationships. The results demonstrate that fashion trends and consumptive behavior exert a positive and significant influence on thrift clothing purchasing decisions, both individually and collectively. Together, the examined variables explain 62.3% of the variance in purchasing decisions. The findings indicate that thrift clothing consumption among Generation Z is driven not only by economic considerations but also by responsiveness to fashion developments and the presence of consumptive tendencies. Keywordsi: fashion trends; consumptive behavior; purchase decision; thrift clothing; Generation Z